PERANCANGAN “HOME OFFICE DESK” MINIMALIS DALAM MENSIASATI PANDEMI - Mohammad Anwar Ulum; DS Drajad Wibowo; Sutarya Sutarya (SULUH: Jurnal Seni Desain Budaya, 2022)
The spread of the Covid-19 virus has now spread throughout the world and has affected various fields, one of which is experiencing this influence, namely the field of work where many companies reduce the number of employees and changes in office work systems, such as companies doing remote work systems where workers do office work. from their homes without having to always come to the office. One of the jobs that use the system is a copywriter. In dealing with this, the author took the initiative to design a desk to support this and give the impression that the office stays focused on doing work and can increase productivity at work, with a design that remains comfortable when used and still pays attention to ergonomic values. Using qualitative research techniques with data expressed in the form of words, sentences and pictures, (Sugiyono, 2006; Pratiwi, 2017) designing a minimalist home office desk form that uses a modern style and additional features as support. A product needs to be adapted to the user and the place where the product is placed. This desk product with a minimalist home office desk concept is intended for students, students, and workers. Apart from being a supporter of this desk activity, it can be used as a complement in interior design.